SLEEPY: a comprehensive Python module for simulating relaxation and dynamics in nuclear magnetic resonance - Smith, Albert A.; Zumpfe, Kai (Nature communications, 2025)
Nuclear magnetic resonance is a powerful method for characterizing dynamics of biological systems in a native-like environment. Accurate dynamics characterization, however, often requires simulations of complex NMR experiments. While a number of simulation programs exist for NMR simulation (SIMPSON, Spinach, SpinEvolution), none of these are focused on easy simulation of motional effects on NMR experiments. The SLEEPY Python module makes it straightforward to simulate arbitrary pulse sequences while including both relaxation and exchange processes. SLEEPY furthermore allows simulation of solid-state (static and spinning) and solution NMR experiments, using both truncated and full Hamiltonians (rotating frame/lab frame). We demonstrate its application to a wide variety of experiments, including transverse (T 1 ρ ), and longitudinal relaxation (T 1 ), nuclear Overhauser effect magnetization transfers, recoupling, and paramagnetic effects. We also provide an extensive online tutorial that explains how to use the various capabilities of SLEEPY. This tool can then be used for both better understanding of the impact of dynamics on NMR and in reproduction of experimental results. Simulation is a critical tool in NMR development, and while powerful simulation software exists, simulating dynamic and relaxation effects remains challenging. Here, the authors describe SLEEPY, a Python module to simplify simulation of such effects.